Influence of high austenite stiffness of shape memory alloy on the response of base‐isolated benchmark building. Issue 2 (19th April 2016) - Ghodke, Sharad; Jangid, R.S.
Summary: The influence of high austenite stiffness of shape memory alloy (SMA) on the response of base‐isolated benchmark building has been investigated. Dynamic analysis was performed by solving the governing equations of motion using Newmark‐beta method under three near‐fault earthquake motions. The super‐elastic behavior of SMA was modeled by the Grasser–Cozzarelli model. Structural response parameters such as top‐floor acceleration, base displacement, and base shear were chosen for investigation. Three near‐fault earthquakes with bidirectional ground motions were considered. It was observed that because of high austenite stiffness of SMA, higher accelerations associated with high frequencies are transmitted to the superstructure. The isolation device with high austenite stiffness of SMA excites the higher modes of the base‐isolated structure and thus magnifies the floor accelerations. This phenomenon can be detrimental to the high‐frequency internal equipments mounted in the base‐isolated structure. On the other hand, the high austenite stiffness of SMA does not affect the base displacement and base shear of the base‐isolated structure significantly. Furthermore, the influence of high austenite stiffness of SMA is dependent on the transformation strength of SMA and flexibility of the isolator. Copyright © 2016 John Wiley & Sons, Ltd.